Rhodeus flaviventris, a new bitterling (Teleostei: Cyprinidae: Acheilognathinae) from China - Li, Fan; Arai, Ryoichi; Liao, Te-Yu (Zootaxa, 2020)
Rhodeus flaviventris, a new species, is described from the Le-An River, a tributary flowing into Poyang Lake in the Yangtze River basin, in Jiangxi Province, China. It is distinguished from all congeners by the combination of characters: branched dorsal-fin rays 9 (9–10); branched anal-fin rays 9 (9–10); longest simple rays of dorsal and anal fins thick and stiff; longitudinal scale series 33–34; transverse scale series 11 (10–12); pored scales 4–7; vertebrae 32–34; spindle-shaped eggs with major axis of 3.1–3.7 mm; color pattern of nuptial males (iris yellowish, belly yellow, central part of caudal fin orange, dorsal and anal fins with reddish-orange stripe).